Approche SIG Pour La Modélisation Du Réseau Routier Et La Mesure De L’accessibilité Aux Équipements Publics. Cas De La Ville d’Agadir - Charaf eddine Benichou; Mokhlis Derkaoui Alaoui; Ali Faleh (European Scientific Journal, ESJ, 2018)
The study of road networks and accessibility to public facilities in Morocco doesn’t receive enough importance in regional planning. Most of the work carried out in the field is limited to diagnosis, relying on traditional tools of analysis and description. The goal of this article is to propose a thorough analysis of public facilities accessibility using isochronous maps, which will not only make it possible to evaluate the quality of urban transport system, but also guarantee the equity of the geographical distribution of public services. The study area is the urban commune of Agadir city on Morocco’s southwest coast. The approach used for this purpose is based on urban road network modeling, travel time calculations and geographic information software (GIS). Therefore, a Geographical Information System dedicated to Transport (GIST) was built, supplied with structured data in a geodatabase, and analyzed by using ArcGIS Network Analyst extension. The results demonstrate that Access to public facilities in the city of Agadir differs in quality according to districts and the types of services. However, the most remote marginal areas remain the most affected areas, both in terms of equipment distribution. the availability of transport infrastructure, or the quality of service in urban public transport.